The many faces of gastrointestinal dysfunction in stiff person syndrome spectrum disorders - Koshorek, Jacqueline; Wang, Yujie; Maldonado, Daniela Pimentel; Reyes-Mantilla, Maria I.; Obando, Danielle; Balshi, Alexandra; Comisac, Michael; Pasricha, Pankaj Jay; Newsome, Scott D. (Frontiers in Neurology, 2023)
Introduction The effect of stiff person syndrome spectrum disorders (SPSD) on the gastrointestinal tract (GIT) is unknown. This case series aims to characterize the prevalence and types of GI dysfunction in individuals with SPSD. Methods A retrospective chart review included individuals diagnosed with SPSD with descriptors of GI symptoms in their medical records. SPSD phenotypes, type of motility test performed, and dysmotility pattern (upper, lower, or diffuse) were assessed. Descriptive statistics and univariate chi-square analyses were utilized. Results Of 240 individuals with SPSD, 32% reported GI symptoms, most were female (83.1%), and white (74%), with a median age at time of GI symptom onset of 50 ± 13 years. Most common symptoms reported were dysphagia (45%), constipation (40%), and nausea/vomiting (23%). Most individuals had classic SPS (47%) followed by SPS-plus (29%) and 82.9% were positive for serum antiGAD65 antibodies. Of 36 patients that underwent at least one GI motility test, 26 had evidence of upper, lower, or diffuse GI dysmotility (44.4%, 17%, and 4%, respectively). The group who did not undergo testing had a higher proportion of patients with DM. Discussion There is a high prevalence of GI symptoms and transit abnormalities in patients with SPSD. Future prospective, longitudinal studies are warranted to further assess GI symptoms in the context of SPSD and to determine if individuals with GI symptoms differ in prognosis or treatment response from those without GI symptoms. In the meantime, there should be a low threshold for motility testing in patients with SPSD.